UPAYA PENINGKATAN PASSING ATAS BOLA VOLI DENGAN MEDIA BOLA PLASTIK DI SDN 05 SENAKIN - Sairen, .; ., Victor; ., Fitriana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractProblems were students at the time of passing over find it difficult to learn because of the standard ball, a lack of means at the time of study and the absence of modification of the tool when learning volleyball. The purpose of this study to determine the increase in passing on the plastic ball media on the remaining fourth grade at SDN 05 Senakin. The method used is classroom action research methods. The subject is the fourth grade students at SDN 05 Senakin 27 learners. Based on the results of the study in the first cycle has been completed there were 13 people (48.2%) and 14 (51.8%) of students who have not completed. While on the second cycle, the students numbering 27 people (100%) of students that have been completed, which means no more students who have not completed the passing of learning on volleyball.Keywords: Passing Over, Media Ball Plastics